Uncovering Ce-rich clusters and their role in precipitation strengthening of an AE44 alloy. (15th July 2023) - Schwarz, Tim M.; Yu, Wenhao; Zhan, Hongyi; Gault, Baptist; Gourlay, Christopher M.; McCarroll, Ingrid
Abstract: The peak-aged (250°C for 4 h) magnesium-aluminum-rare earth (Mg-Al-RE) alloy AE44-2 produced using high-pressure die casting, exhibits a 10 % increase in yield strength attributed to the formation of nanoscale AlMn precipitates. Here, in the as cast state, we show by atom probe tomography Ce-rich clusters in the dendritic and not in the inter-dendritic α-Mg, despite a higher RE concentration. Their formation hence depends mainly on solidification kinetics and not on the concentration. The Ce-rich clusters within the dendritic region, act as heterogeneous nucleation sites for the formation of Al10 Mn7 RE2 nanoscale precipitates during the T5 heat treatment. No changes in the Al11 RE3 lamella phase were observed, including to the concentration of segregated Si at the Al11 RE3 /α-Mg interface. Understanding the precipitate formation pathways, specifically the influence of low concentrations of Ce in the dendritic matrix, provides a pathway for tailoring mechanical properties by manipulating these clusters and consequently precipitation. Graphical abstract: Image, graphical abstract